2021
DOI: 10.1093/ptep/ptab030
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new tracking detector with fine-grained nuclear emulsion for sub-MeV neutron measurement

Abstract: In this study, we have developed a new sub-MeV neutron detector that has a high position resolution, energy resolution, directional sensitivity, and low background. The detector is based on a super-fine-grained nuclear emulsion, called the Nano Imaging Tracker (NIT), and it is capable of detecting neutron induced proton recoils as tracks through topological analysis with sub-micrometric accuracy. We used a type of NIT with AgBr:I crystals of (98 ± 10) nm size dispersed in the gelatin. First, we calibrated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…4(c) reports the neutron energy reconstructed through the recoil-proton energy and the scattering angle, with a peak value at (864 ± 46) keV, consistent with the exposure energy. The obtained energy resolution is ∆E n,FWHM /E n = 0.31 for 880 keV neutrons, comparable to the value of 0.42 measured in the previous calibration run for 540 keV neutrons 2 .…”
Section: B Three Dimensional Sub-micrometric Tracking Systemsupporting
confidence: 85%
See 2 more Smart Citations
“…4(c) reports the neutron energy reconstructed through the recoil-proton energy and the scattering angle, with a peak value at (864 ± 46) keV, consistent with the exposure energy. The obtained energy resolution is ∆E n,FWHM /E n = 0.31 for 880 keV neutrons, comparable to the value of 0.42 measured in the previous calibration run for 540 keV neutrons 2 .…”
Section: B Three Dimensional Sub-micrometric Tracking Systemsupporting
confidence: 85%
“…In a previous work 2 , we reported that the energy measurement through Eq. 2 showed an accuracy of ∆E n,FWHM /E n = 0.42 for 540 keV neutrons.…”
Section: B Three Dimensional Sub-micrometric Tracking Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all dark matter detectors, the presence of H in NIT is a unique feature. This makes NIT a particularly efficient neutron detector using proton recoil tracking [19,20]. The tracking capability of detecting nuclear recoils corresponding to 30 keV Carbons [21] and 10 keV protons has been demonstrated by ion doping with an ion-implantation system in Japan (to be published for low-energy proton tracking around 10 keV), while the use of Ultra-NIT (U-NIT) with 20 nm AgBr diameters can lower the threshold for carbon recoils down to 10 keV.…”
Section: Super-fine-grained Nuclear Emulsionmentioning
confidence: 99%
“…Fine-grained nuclear emulsions with silver halide crystals having a diameter of less than 0.1 µm have been developed [31][32][33] to detect the tracks of the nuclei recoiled by the so-called weakly interacting massive particles. The sensitivity of the nuclear emulsion was optimised to track the nuclei but was maintained sufficiently low for electrons and γ-rays 34 . This type of fine-grained nuclear emulsion can be used for neutron imaging by combining it with the 10 B 4 C thin layer, which absorbs neutrons and emits charged particles heading in the opposite direction via the following process: 10 B + n → 7 Li + 4 He.…”
Section: Introductionmentioning
confidence: 99%